Matter-element evaluation of ecological quality in gaps of temperate secondary forests - Hui Liu; Xibin Dong; Shili Qin; Tong Gao (Ecological Indicators)
Forest gaps play a crucial role in facilitating the recovery and succession of forest ecosystems. The ecological quality of forest gaps has emerged as a key research focus, particularly for their capacity to maintain biodiversity, productivity, resilience, and facilitate nutrient cycling and resource provision. In 2009, gaps of various sizes were established across three types of secondary forests in the Greater Khingan Mountains. This study employed a combination of the improved combination weight method from game theory and the matter-element extension model to evaluate the ecological quality of these forest gaps. Furthermore, 43 factors were analyzed, including soil physicochemical properties, litter water retention capacity, canopy structure, photosynthetic parameters, species diversity, growth and survival rates of planted trees, and the annual growth of retained trees. This comprehensive analysis aimed to elucidate the ecological quality status in the region and to reveal the interrelationships and mechanisms at play. The results indicated that soil physicochemical properties, the degree of litter decomposition and accumulation, canopy openness, and leaf area collectively accounted for a weight of 86.42%, identifying them as critical indicators influencing ecological quality. Among the litter characteristics, the accumulation of semi-decomposed material emerged as a primary factor influencing litter water retention capacity. Additionally, leaf surface radiation flux represented the largest proportion of the photosynthetic parameters at 29.75%. Overall, the forest gaps in Betula platyphylla and Quercus mongolica forests exhibited excellent quality, with wide strip-shaped gaps yielding the most favorable effects. The overall gap quality in plots containing Larix gmelinii and Pinus koraiensis was also rated as excellent, highlighting the significant role of these gaps in enhancing ecological quality.